Unveiling Peutz-Jeghers Syndrome in the Fourth Decade: A Rare Case of Colorectal-Predominant Polyposis and High-Grade Dysplasia without Pathognomonic Pigmentation - Fuadhi Rifky; Albertus Ari Adrianto; Martahadinan (HM Publisher, 2026)
Background: Peutz-Jeghers syndrome (PJS) is a rare autosomal dominant condition characterized by gastrointestinal hamartomatous polyposis and mucocutaneous pigmentation. While typically presenting in childhood with small bowel predominance, adult-onset cases lacking classical phenotypic markers present severe diagnostic challenges. Case presentation: A 41-year-old male with no significant family history presented with a six-month history of progressive constipation, altered stool caliber, and hematochezia. Clinical examination revealed an absolute absence of pathognomonic mucocutaneous pigmentation. Abdominal imaging and full colonoscopy demonstrated an extensive colorectal polyposis burden extending from the rectosigmoid junction to the caecum. Histopathology of the resected tissue confirmed hamartomatous polyps featuring arborizing smooth muscle cores alongside focal high-grade dysplasia. The patient successfully underwent an elective total proctocolectomy with an ileal J-pouch anal anastomosis and a diverting loop ileostomy. Postoperative recovery was completely unremarkable. Conclusion: This case underscores the profound phenotypic heterogeneity of PJS. The presence of an extensive colorectal burden and high-grade dysplasia in an adult lacking mucocutaneous pigmentation highlights the definitive malignant potential of hamartomatous polyps and the critical necessity for prompt surgical intervention and tailored surveillance in atypical clinical presentations.